2006
DOI: 10.1021/jp056362g
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Kinetic Modeling Study of the Effects of Oxygenated Hydrocarbons on Soot Emissions from Diesel Engines

Abstract: A detailed chemical kinetic modeling approach is used to examine the phenomenon of suppression of sooting in diesel engines by addition of oxygenated hydrocarbon species to the fuel. This suppression, which has been observed experimentally for a few years, is explained kinetically as a reduction in concentrations of soot precursors present in the hot products of a fuel-rich diesel ignition zone when oxygenates are included. Oxygenates decrease the overall equivalence ratio of the igniting mixture, producing hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
276
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 491 publications
(289 citation statements)
references
References 59 publications
13
276
0
Order By: Relevance
“…A chemical kinetic model for TPGME has been developed previously [1,11] to address its hightemperature chemistry and production of soot precursor species under conditions in diesel engines (high pressures 99 atm and low temperatures 767 K), and this model also took the surrogate approach, by only considering the isomer shown in Fig. 2.…”
Section: Figure 2: Isomer 3a Chosen To Represent Tpgme Mixture For Momentioning
confidence: 99%
See 2 more Smart Citations
“…A chemical kinetic model for TPGME has been developed previously [1,11] to address its hightemperature chemistry and production of soot precursor species under conditions in diesel engines (high pressures 99 atm and low temperatures 767 K), and this model also took the surrogate approach, by only considering the isomer shown in Fig. 2.…”
Section: Figure 2: Isomer 3a Chosen To Represent Tpgme Mixture For Momentioning
confidence: 99%
“…2. Westbrook et al [11] presented comparisons of a range of oxygenated fuel additives (methanol, ethanol, dimethyl ether, dimethoxy methane, methyl butanoate, TPGME, dimethylcarbonate and DBM) and their effect on the formation of soot precursor species (ethylene, acetylene, propyne, etc.). It was found that the formation of these species was somewhat reliant on the percentage oxygen by weight in the overall fuel mixture (n-heptane + oxygenated additive in "air").…”
Section: Figure 2: Isomer 3a Chosen To Represent Tpgme Mixture For Momentioning
confidence: 99%
See 1 more Smart Citation
“…The state of the art ethanol oxidation mechanism constructed by Marinov 21,22 predicts that a significant fraction of ethanol undergoes hydrogen atom abstraction from the methyl group (Reaction 7):…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of Glaude et al indicates that most of the oxygen in the dimethyl carbonate goes into the direct production of CO 2 via dissociation of the methoxy carbonyl radical. Both Glaude 6 and Westbrook 21 remark that direct production of CO 2 in the combustion of oxygenated fuels is not an ideal utilization of oxygen because only one C atom per every two O atoms has been prevented from forming carbon-carbon bonds that characterize soot precursors.…”
Section: Introductionmentioning
confidence: 99%